Determinants of Drug-Induced Hepatotoxicity Among Patients with Human Immunodeficiency Virus Taking a High Dose of Rifapentine Plus Isoniazid Drugs at the All Africa Leprosy Tuberculosis Rehabilitation and Training Center in Addis Ababa, Ethiopia - Lisanwork Arage L (Dove Medical Press, 2021)
Leuel Lisanwork Arage,1 Haji Aman Deybasso,2 Delelegn Yilma Gebremichael,3 Binyam Gintamo Nuramo,4 Zelalem Negash Mekuria4 1The Ohio State University Global One Health, Addis Ababa, Ethiopia; 2Adama Hospital Medical College, Adama, Ethiopia; 3Ambo University, College of Medicine and Health Sciences, Department of Public Health, Ambo, Ethiopia; 4Addis Ababa Medical and Business College, Department of Research and Community Service, Addis Ababa, EthiopiaCorrespondence: Haji Aman Deybasso Tel +251 911386781Email hajia.aman9@gmail.comPurpose: The drugs for the treatment of latent Tuberculosis are potentially hepatotoxic and can lead to drug-induced hepatotoxicity. The current study aimed at identifying the determinants of anti-tuberculosis drug-induced hepatotoxicity among patients living with Human Immunodeficiency Virus taking Isoniazid and rifapentine at All Africa Leprosy Tuberculosis Rehabilitation and Training Center in Addis Ababa, Ethiopia.Methods: An unmatched case–control study was conducted from March, 21, to April 21, 2020, at All Africa Leprosy Tuberculosis Rehabilitation and Training Center. A total of 65 cases and 130 controls were interviewed. Data were collected using a data extraction tool from clinical reporting forms, follow-up charts, and patients’ logbooks. Binary and multiple logistic regressions were conducted to check the association between independent and dependent variables. Adjusted odds ratios and the corresponding 95% confidence intervals were estimated to assess the strength of association. P-values < 0.05 were used to declare statistical significance.Results: The prevalence of anti-TB drug-induced hepatotoxicity was 8%. Body mass index < 18.5 Kg/m2 (AOR = 5.8 [95% CI: 2.2– 8.9]), low CD4 count (AOR = 4.9 [95% CI: 1.6– 15.8]), and the presence of comorbid illnesses (AOR = 3.9 [95% CI: 1.7– 8.9]) were identified as independent predictors of drugs-induced hepatotoxicity among Human Immunodeficiency Virus positive patients taking Isoniazid and rifapentine.Conclusion: The prevalence of anti-TB drug-induced hepatotoxicity was higher compared to standard references. BMI< 18 kg/m2, low CD4 count, and comorbid illness were positively associated with anti-tuberculosis drug-induced hepatotoxicity among patients with HIV.Keywords: isoniazid and rifapentine, TPT, hepatotoxicity, HIV patients, Ethiopia